Reference intervals for canine hematologic analytes using Siemens Advia 120 - OIKONOMIDIS, I. L.; TSOULOUFI, T. K.; PAPOUTSI, A.; KRITSEPI-KONSTANTINOU, M. (Journal of the Hellenic Veterinary Medical Society, 2018)
Hematologic investigation is essential for the evaluation of health status of companion animals. Appropriate and accurate reference intervals (RIs) are required for the interpretation of laboratory results. Thus, the primary aim of the present study was to establish canine complete blood count (CBC) RIs using Advia 120, a widely used in veterinary medicine automated hematology analyzer. Additional objectives were to evaluate sex as a partitioning factor of RIs and to investigate the effect that breed size has on CBC RIs. Reference individuals were selected by indirect sampling method from the medical records of a veterinary teaching hospital. The reference population comprised 284 adult dogs of both sexes and various breeds. The reference individuals were allocated into 3 groups based on breed size (small-sized, medium-sized and large-sized breeds). Complete blood count results from the dogs that met the inclusion criteria were used for the nonparametric calculation of RIs. Statistical and nonstatistical criteria were employed in order to decide whether sex-specific RIs are needed. Depending on the data distributions, mean or median comparisons were used to determine the effect of breed size and lifestyle on CBC results. Nine outliers were detected based on CBC results. The estimated RIs were generally comparable to those previously reported in the literature. Sex-dependent partitioning of RIs was indicated by the statistical criteria for a few analytes. From a clinicopathologic point of view though, sex-dependent partitioning of RIs is questioned and seems not to be required. Breed size appears to have an effect on CBC RIs. The RIs determined in the present study can be used as a guide for the interpretation of CBC results in dogs and can potentially be adopted by veterinary laboratories using Advia 120. Finally, based on the results of this study, breed size should probably be considered when interpreting CBC results.